Development and Evaluation of Digital ID card as a Portfolio Portal - Erico Darmawan; Sulaeman Santoso (Universitas Multimedia Nusantara, 2018)
Physical ID card has been use throughout history and are still widely use today. However, suchphysical characteristic leads to three drawbacks. First, it is not environmentally friendly due to printed materials. Second, Physical ID card requires the need for management and physical storage, prone to damage and lost. Third, information inside a physical ID card limited and cannot be updated. This paper proposes the use of digital ID card in the form of a mobile application as a substitute to physical ID card. A survey is conducted to evaluate the use of these digital ID card. It is then concluded that digital ID card can counter the downside of physical ID card and even provides features to enhance its role such as being a portal for information. Keywords—Digital ID, Information Portal, Mobile Application, Android.